2017
DOI: 10.3892/etm.2017.4099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-emptive analgesia by continuous femoral nerve block on early postoperative cognitive function following total knee arthroplasty in elderly patients

Abstract: Abstract. To the best of our knowledge, the effect of pre-emptively blocking pain transmission on acute postoperative cognitive dysfunction (POCD) has not yet been assessed. Therefore, the present study aimed to investigate the effect of pre-emptive analgesia via a continuous femoral nerve block (CFNB) on postoperative pain and early cognitive function following total knee arthroplasty (TKA) surgery in elderly patients. CFNB was performed prior to TKA surgery in the preemptive analgesia group (n=30) and follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…MMSE is one of the most widely used scales in evaluating cognitive function, and a previous study defined POCD as a postoperative MMSE score >1 standard deviation below the preoperative score [24]. Deng et al used the MMSE score >1 standard (equal to 2 points) and reported that preemptive use of cFNB could enhance the recovery of cognitive function in patients undergoing TKA surgery [11]. We also adopted the latter criteria and achieved similar results.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…MMSE is one of the most widely used scales in evaluating cognitive function, and a previous study defined POCD as a postoperative MMSE score >1 standard deviation below the preoperative score [24]. Deng et al used the MMSE score >1 standard (equal to 2 points) and reported that preemptive use of cFNB could enhance the recovery of cognitive function in patients undergoing TKA surgery [11]. We also adopted the latter criteria and achieved similar results.…”
Section: Discussionmentioning
confidence: 57%
“…As previously described [11], supine position was placed for patients of cFNB group the with the target leg a little abducted.…”
Section: Perioperative Analgesiamentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that satisfactory analgesia can decrease the incidence of POCD following total knee arthroplasty (TKA) in geriatric patients. ( 23 ) Animal studies demonstrated that postoperative pain might cause memory deficits ( 24 ), and such effects were reversed by a non-steroidal anti-inflammatory drug via its analgesic effects in animals ( 25 ). In the present study, celecoxib did not show an additional advantage of analgesia within 48 h post-surgery due to the efficiency of PCA.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative cognitive dysfunction often leads to mental disorders, personality changes, memory loss, anxiety and other mental symptoms, which is caused by central nervous system damage due to surgery or anesthesia, seriously affecting the life quality of patients ( 1 , 2 ). It has been reported that the commonly-used anesthetics, such as isoflurane and ketamine, can cause postoperative cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%